2014
DOI: 10.1002/cbic.201402288
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Trehalose Analogues: Rapid Access to Chemical Probes for Investigating Mycobacteria

Abstract: Trehalose analogues are emerging as valuable tools for investigating Mycobacterium tuberculosis, but progress in this area is slow due to the difficulty in synthesizing these compounds. Here, we report a chemoenzymatic synthesis of trehalose analogues that employs the heat-stable enzyme trehalose synthase (TreT) from the hyperthermophile Thermoproteus tenax. By using TreT, various trehalose analogues were prepared quickly (1 h) in high yield (up to >99 % by HPLC) in a single step from readily available glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 33 publications
(15 reference statements)
1
84
0
Order By: Relevance
“…Thus, this work established a robust method for the rapid and convenient synthesis of fluorine-modified trehalose analogues, confirmed that the analogues mimic the structure of native trehalose, and demonstrated that they could bind to mycobacteria through a non-mammalian trehalose recycling pathway. Together, the pioneering work of the Barry and Davis groups, 52,115 combined with our contributions, 82,83 should help to pave the way for continued development of trehalose-based PET imaging probes for tuberculosis diagnostics and other applications.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 93%
See 4 more Smart Citations
“…Thus, this work established a robust method for the rapid and convenient synthesis of fluorine-modified trehalose analogues, confirmed that the analogues mimic the structure of native trehalose, and demonstrated that they could bind to mycobacteria through a non-mammalian trehalose recycling pathway. Together, the pioneering work of the Barry and Davis groups, 52,115 combined with our contributions, 82,83 should help to pave the way for continued development of trehalose-based PET imaging probes for tuberculosis diagnostics and other applications.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 93%
“…In our initial report in 2014, we showed that this enzyme could indeed convert a wide variety of glucose analogues to trehalose analogues in high yield (up to 99% yield as determined by HPLC, Figure 7). 82 The method has now been applied to the semi-preparative synthesis of numerous analogues bearing a variety of modifications (e.g., fluoro-, deoxy-, azido-, thio-, stereochemical, and isotopic modifications), with typical isolated yields of 60–80%. 8284 The rapid and facile procedures we have developed for TreT-catalyzed synthesis and product purification have facilitated access to novel trehalose analogues for mycobacteria research, as discussed in more detail later.…”
Section: Approaches To Trehalose Analogue Synthesismentioning
confidence: 99%
See 3 more Smart Citations